Genero y especie nuevas de la tribu stigmoderini (Coleoptera): Buprestidae) en America - Moore, T.=700 1 Lander, T.
(En, Es)
ilus., 2 ref.
Keywords: BUPRESTIDAE; COLEOPTERA; ESPECIES NUEVAS; REGION NEOTROPICAL; BRASIL; GENERO; STIGMODERINI; ESPECIE; SEMIOGNATHA